2011
DOI: 10.1002/hed.21401
|View full text |Cite
|
Sign up to set email alerts
|

Impact and management of airway obstruction in patients with squamous cell carcinoma of the larynx

Abstract: After appropriate management of airway obstruction, the postoperative complications and oncologic results were similar to those without airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This is despite the fact that over the last 20 years, there have been monumental changes in the management of laryngeal cancer. These have included major changes in treatment paradigms, resulting in a major shift toward primary nonsurgical management of most locally advanced laryngeal cancers; advances in radiotherapy techniques, including improvements in treatment planning and combination with chemotherapy; and advances in laser microsurgery with increasing use of laser for definitive treatment of early laryngeal cancers, as well as allowing endoscopic debulking of obstructive tumors with obviation of need for tracheostomy in many cases . The result of this has been a major change in the profile of cases currently undergoing total laryngectomy, with more advanced primary tumor classification of cases submitted to total laryngectomy, particularly among cases undergoing primary laryngectomy; and a much greater preponderance of salvage over primary surgical cases in most modern series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite the fact that over the last 20 years, there have been monumental changes in the management of laryngeal cancer. These have included major changes in treatment paradigms, resulting in a major shift toward primary nonsurgical management of most locally advanced laryngeal cancers; advances in radiotherapy techniques, including improvements in treatment planning and combination with chemotherapy; and advances in laser microsurgery with increasing use of laser for definitive treatment of early laryngeal cancers, as well as allowing endoscopic debulking of obstructive tumors with obviation of need for tracheostomy in many cases . The result of this has been a major change in the profile of cases currently undergoing total laryngectomy, with more advanced primary tumor classification of cases submitted to total laryngectomy, particularly among cases undergoing primary laryngectomy; and a much greater preponderance of salvage over primary surgical cases in most modern series.…”
Section: Discussionmentioning
confidence: 99%
“…These have included major changes in treatment paradigms, resulting in a major shift toward primary nonsurgical management of most locally advanced laryngeal cancers 16,17 ; advances in radiotherapy techniques, including improvements in treatment planning and combination with chemotherapy; and advances in laser microsurgery with increasing use of laser for definitive treatment of early laryngeal cancers, as well as allowing endoscopic debulking of obstructive tumors with obviation of need for tracheostomy in many cases. 18 The result of this has been a major change in the profile of cases currently undergoing total laryngectomy, with more advanced primary tumor classification of cases submitted to total laryngectomy, particularly among cases undergoing primary laryngectomy; and a much greater preponderance of salvage over primary surgical cases in most modern series. Furthermore, awareness of the possible impact of preoperative tracheostomy on local control has prompted further modifications to management, including recommendations for complete excision of the tracheostomy tract at the time of laryngectomy, central compartment nodal dissection, and postoperative irradiation of the peristomal and upper mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing laryngectomy and pharyngolaryngectomy were also almost six times more likely to undergo surgery during an emergency admission. This finding may be interpreted in a number of ways and could reflect the fact that some patients with advanced laryngeal and hypopharyngeal cancers enter the head and neck cancer pathway following an acute presentation with airway obstruction . All of these observed baseline differences carry prognostic significance.…”
Section: Discussionmentioning
confidence: 90%
“…Performing emergency major surgery worsened all measured outcomes. There is some evidence that effective management of airway obstruction before undertaking laryngectomy may mitigate the impact of airway obstruction on post‐treatment morbidity, but further research is needed to understand the reasons behind the additional morbidity and mortality associated with emergency major surgery, and to devise approaches to mitigate it. It is logical that efforts to recognise and refer patients before airway obstruction, and improved pre‐habilitation of patients who present as emergencies prior to major surgery may play a role in improving the outcome but the impact of such interventions need to be systematically studied.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports in the literature with no consensus on the issue [1, 36, 1214]. However in one study reported by Menedhall et al in patients with T3 transglottic carcinoma the tumor bulk was taken into account by CT volumetric estimation, yet pretreatment tracheostomy was significantly related to diminished cause-specific survival ( P = 0.0345).…”
Section: Discussionmentioning
confidence: 99%